Inquiry of cases of myiasis by Cochliomyia hominivorax in dogs (Canis familiaris) of the Northern and Western zones of Rio de Janeiro city in 2000 - Cramer-Ribeiro, Bianca Chiganer; Sanavria, Argemiro; Monteiro, Heloísa Helena Magalhães Soares; Oliveira, Marcelo Queiroz de; Souza, Fábio Silva de (Brazilian Journal of Veterinary Research and Animal Science, 2003)
An inquiry about cases of myiasis by C. hominivorax larvae on dogs presented to 190 veterinary establishments of Rio de Janeiro City in 2000 was performed to contribute to the comprehension of epidemiological features of this myiasis. Cases of screwworm infestation were observed in 184 veterinary establishments: in 104 among 108 establishments of the Northern Zone, and in 80 of 82 establishments of the Western Zone of the city. Most infested dogs were adult, pure breed, long and dark-haired, living in houses, while no preference for sex was observed. Ears were most infested, and the main cause of lesions that led to myiasis was otitis. Screwworm infestation is a very frequent disease on dogs, and prevention programs should be developed, specially during hot weather months (December and January), when incidence was higher. Most infested dogs are the ones that need more care, and prevention of all possible causes of myiasis will help its avoidance. Dirt and lack of hygiene are also causes of screwworm infestation and must be avoided, as other myiasis causes. Pet owners negligence is a contributing factor to the appearance of screwworm infestation on dogs, and pet owners should receive orientation from veterinary clinicians. Additional studies about screwworm infestation on dogs should be performed, in order to identify more predisposing factors to be used in prevention programs.